Perceived Impacts of the COVID-19 Pandemic on Pediatric Care in Canada: A Roundtable Discussion - David B. Nicholas PhD; Mark Belletrutti MD; Gina Dimitropoulos PhD; Sherri Lynne Katz MDCM, MSc, FRCP(C); Adam Rapoport MD, MHSc, FRCP(C); Simon Urschel MD; Lori West MD, DPhil; Lonnie Zwaigenbaum MD, FRCP(C) (Global Pediatric Health, 2020)
Like other recipients of health care services, pediatric patients and their families/caregivers have been profoundly impacted by health care shifts and broader societal restrictions associated with the COVID-19 pandemic. An online roundtable discussion was facilitated with 7 pediatric clinicians and investigators of a current study examining the impacts of COVID-19 on pediatric care at multiple Canadian sites. Discussants represented a range of pediatric specialities: developmental disability, mental health, cardiac transplantation, respiratory medicine, hematology, and palliative care. We offer the transcript of the roundtable in which discussants reflected on clinical and programmatic experiences of the pandemic, including perceived impacts on children receiving care and their families, potential opportunities for improved health care delivery, impacts on health care providers, and recommendations as we move toward easing restrictions and pandemic recovery. Discussants convey a range of considerations that may have varying relevance for pediatric specialities in terms of practice and program planning.